Efisiensi Teknis Produksi Tandan Buah Segar (TBS) Kelapa Sawit: Studi pada Afdeling I dan II Kebun S PTPN IV Regional V, Kalimantan Barat - Ardiano, Nikolas; Yurisinthae, Erlinda; Fitrianti, Wanti (Politeknik Negeri Lampung, 2026)
Oil palm production efficiency plays a crucial role in maintaining productivity and sustainability amid fluctuating yields and increasing input use. This study aims to measure the technical efficiency of palm oil production at PT Perkebunan Nusantara IV Regional V West Kalimantan, one of the largest plantations in the region. The method employed is non-parametric statistics, utilizing Data Envelopment Analysis (DEA) with an output-oriented approach and the Variable Return to Scale (VRS) assumption, based on panel data spanning five years (2019–2023). The study encompasses two divisions (Afdeling I and II), each comprising six different planting years to represent variations in plant age and productivity. Input variables include land area, labor, number of trees, NPK fertilizer, and plant age, while the output variable is fresh fruit bunch (FFB) production. The results showed that most plantation divisions with old and young planting years experienced production inefficiencies. Technical inefficiency is influenced by the distribution and management of inputs that are not yet optimal, as well as by the decline in plant population due to pest and disease attacks. These findings offer valuable insights for enhancing input allocation, optimizing field management, and promoting the sustainability of palm oil production in the future.